ASSESSMENT OF SOURCES OF INFORMATION AND CONSTRAINTS ASSOCIATED WITH GROUNDNUT PRODUCTION AND POST-HARVEST VALUEADDITION AMONG FARMERS IN GOMBE STATE. - G., ERASMUS; M. E., SULAI (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
The study was conducted to assess sources of information and constraints associated with groundnut production and post-harvest value-addition among farmers in Gombe State, Nigeria. Multistage, purposive and simple random sampling techniques were used to select a sample size of 159 respondents. Data collected using a structured questionnaire were analyzed. Descriptive and inferential statistical tools like frequency, percentages and logistic regression were used for analysis. The result showed that 43.4% of the respondents had Grade 11/ Secondary education About 43% had household size of 5 -10 persons and 34.6% had farming experience of 6 -10 years. About 71% of the respondents had annual income of less than ₦100,000 from sales of groundnut and its products per annum. Result on skills acquired on value-addition of groundnut production and processing shows that 30.2% of the respondents acquired skills on toasting peanut. Result on products obtained from processing groundnut shows that 61.6% obtained oil as their product. The study concludes that if farmers’ level of education and experience are increase there will be increase in value-addition. Based on the findings, it is recommended that skills on groundnut value –chain should be taught to the farmers by the extension agents and government agencies. Keywords: